Financial Literature to Sustainbility Micro Business in Gowa Regency - Serly Serly; Anwar Anwar; Nurman Nurman (PINISI Discretion Review, 2022)
This research is a qualitative research that aims to find out how the level of financial literacy on the sustainability of Micro Enterprises in Gowa Regency. The sample in this study consisted of 5 informants of micro business actors. Techniques for analyzing research data using the help of ATLAS.ti 9. The results of the analysis show that micro-enterprises are classified as not literate, so the financial literacy of micro-enterprises is still lacking. It can be concluded that micro-enterprises have no potential for business sustainability.